2022
DOI: 10.1186/s12916-022-02431-z
|View full text |Cite
|
Sign up to set email alerts
|

Is living in a household with children associated with SARS-CoV-2 seropositivity in adults? Results from the Swiss national seroprevalence study Corona Immunitas

Abstract: Background We aimed to determine whether living in a household with children is associated with SARS-CoV-2 seropositivity in adults and investigated interacting factors that may influence this association. Methods SARS-CoV-2 serology testing was performed in randomly selected individuals from the general population between end of October 2020 and February 2021 in 11 cantons in Switzerland. Data on sociodemographic and household characteristics, emp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…As the study was conducted during the coronavirus disease 2019 (COVID-19) pandemic, due to the transmission of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), the presence of SARS-CoV-2 antibodies was chosen as a second respiratory health outcome. SARS-CoV-2 immunoglobulin G (IgG) antibodies become detectable in most cases around 6–15 days after symptom onset [ 20 ]. Sera extracted from the participants’ venous blood were analyzed using SenASTrIS (Sensitive Anti-SARS-CoV-2 Spike Trimer Immunoglobulin Serological), a Luminex binding assay [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the study was conducted during the coronavirus disease 2019 (COVID-19) pandemic, due to the transmission of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), the presence of SARS-CoV-2 antibodies was chosen as a second respiratory health outcome. SARS-CoV-2 immunoglobulin G (IgG) antibodies become detectable in most cases around 6–15 days after symptom onset [ 20 ]. Sera extracted from the participants’ venous blood were analyzed using SenASTrIS (Sensitive Anti-SARS-CoV-2 Spike Trimer Immunoglobulin Serological), a Luminex binding assay [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Indeterminate test results, meaning a signal just below the predefined cutoff, were retested, and when confirmed, “indeterminate” was counted as negative. The test has a high specificity (99.7%) and sensitivity (96.6%) and has been validated in samples of the general population as well as specific subgroups of people [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Roche rapid test (20) Orient Gene Biotech (42) SenASTrIS test (97,98) Siemens Advia Centaur (52,99) Siemens Advia anti-RBD Vitros Ortho (not total antibodies) (13,(104)(105)(106)(107) Vitros Ortho (total antibodies) (13,14) Wantai (14,69,108,109)…”
Section: Estimation Of Testing Timesmentioning
confidence: 99%
“…Vaccination has a double effect: direct protection of vaccinated individuals and indirect protection of individuals living in vaccinated environments (12). Several studies reported that a substantial amount of COVID-19 transmission occurs in close, crowded, and prolonged contact, such as in households (13)(14)(15)(16). These household studies may be alternatives to larger populations for estimating the direct and indirect effects of vaccines (12).…”
Section: Introductionmentioning
confidence: 99%